Pretopological Spaces Induced by Rough Sets and Their Applications (European Journal of Pure and Applied Mathematics, 2025)
In this paper, we generate pretopological spaces from a binary relation. We introduce a new approximation space by using pretopological concepts. Some properties and the comparison among different types of lower approximation and the upper approximation are studied. We introduce an application of pretopological spaces in rough approximation. some generalizations of rough sets concepts based on pretopological space are introduced.